Effect of a perceived threat of informal actors on the business performance of formal actors: inbound tour operators' perspective - Mwesiumo, Deodat; Juma Abdalla, Moh'd; Ozturen, Ali; Kilic, Hasan (Routledge Journals, Taylor & Francis Ltd, 2021)
This paper develops and tests a conceptual model to examine the effect of a perceived threat of informal actors on the business performance of formal actors. Drawing on a sample of 130 inbound tour operators, structural path analysis shows that the perceived threat of informal actors is positively associated with the formal actors' service quality and customer acquisition efforts, which subsequently are positively associated with an increase in business performance. The perceived threat of informal actors appears to increase business performance only through its influence on service quality and customer acquisition efforts. Based on the findings, actionable recommendations are provided.
Keywords: Tourism; informal actors; formal actors; tour operators; service quality; customer acquisition efforts; business performance